Heavy metal in paddy soil and its bioavailability in rice using in vitro digestion model for health risk assessment - Zulkafflee, Nur Syahirah; Mohd Redzuan, Nurul Adillah; Hanafi, Zanjabila; Selamat, Jinap; Ismail, Mohd Razi; Praveena, Sarva Mangala; Abdull Razis, Ahmad Faizal (MDPI, 2019)
Rice ingestion is one of the major pathways for heavy metal bioaccumulation in human. This study aimed to measure the heavy metal content of paddy soils and its bioavailability in paddy grain in order to assess the health risk. In total, 10 rice samples (50 g each) of paddy plants were harvested from the Selangor and Terengganu areas of Malaysia to assess the bioavailability of heavy metal (As, Cd, Cu, Cr, and Pb) using the in vitro digestion model of Rijksinstituut voor Volksgezondheid en Milieu. The bioavailability of heavy metal concentrations in rice samples were analyzed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The findings showed the bioavailability of heavy metal concentrations was decreased in the order Cr > Cu > Pb > As > Cd. Chromium was found to be the most abundant bioavailable heavy metal in cooked rice, which was the result of its high content in paddy soil. Hazard Quotient values for the bioavailability of the heavy metal studied were less than one indicating no non-carcinogenic health risks for adults and children. Meanwhile, the total Lifetime Cancer Risk exceeded the acceptable value showing a potential of carcinogenic health risk for both adults and children. The application of in vitro digestion model in assessing bioavailability of heavy metal produces a more realistic estimation of human health risks exposure. However, a regular monitoring of pollution in Selangor and Terengganu areas is crucial since the exposure of heavy metals through rice consumption poses the potential non-carcinogenic and carcinogenic health risk to the local residents.